2020
DOI: 10.2116/analsci.19p465
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Comparison of Antibody-drug Conjugates Based on Good Manufacturing Practice Strategies

Abstract: The production of antibody-drug conjugates (ADCs) has been in great demand in the field of cancer therapeutics. Although cysteine-based conjugation is the most common and well known process for producing ADCs, multiple analytical methods are required for accurate drug-antibody ratio (DAR) determination due to the heterogeneity of the ADCs. Here we report various analytical methods for DAR analysis of traditional cysteine-based ADCs; additionally, apply a good manufacturing practice (GMP) strategy to produce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…A reaction time course investigation and a temperature dependency study was conducted based on a previously reported approach (Scheme 1) [15,16,17] . The first step of this conjugation is the TCEP-mediated partial reduction of the antibody's interchain disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reaction time course investigation and a temperature dependency study was conducted based on a previously reported approach (Scheme 1) [15,16,17] . The first step of this conjugation is the TCEP-mediated partial reduction of the antibody's interchain disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The first step of this conjugation is the TCEP-mediated partial reduction of the antibody's interchain disulfide bonds. Free thiols generated in the resulting reduced antibody is an essential factor for DAR of the resulting ADCs [17] . This theory was also confirmed in previous analytical investigations where the free thiols per antibody post-reduction were comparable and predictive of the DAR values measured from the final ADCs [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…HIC-HPLC analysis was performed based on previously reported [21]. Each ADC was analyzed using Tosoh Bio Butyl-NPR 2.5 µm 4.6 × 35 mm column (Tosoh Bioscientific), connected to an Agilent 1260 HPLC system containing a binary gradient pump, a temperature-controlled column compartment, an autosampler, and a diode array detector.…”
Section: Hic-hplc Analysismentioning
confidence: 99%
“…RP-HPLC analysis was performed based on previously reported [21]. Each sample was prepared as follows: 1.0 mg/mL of ADCs in 500 mM tris buffer, pH 8.0, was diluted to 0.6 mg/mL in 8 M guanidine HCl and reduced by the addition of 1 M DL-Dithiothreitol (DTT).…”
Section: Rp-hplc Analysismentioning
confidence: 99%
“…7) Regulatory bodies such as FDA and European Medicines Agency require the biopharmaceutical industry to analyze antibody-small molecule bioconjugates similarly to both large-molecule and small-molecule drugs, and the complex nature of ADCs require well-thought analytical strategies. 8,9) Although many analytical chemists have reported unique methodologies in the scientific literature that are geared toward the establishment of a gold standard technique for DAR characterization, challenges remain because of the structural complexity, diversity and heterogeneity of ADCs. 7,10) In addition to heterogeneity due to conjugation methodology as described above, there is antibody-related issue to be considered.…”
Section: Introductionmentioning
confidence: 99%